Intravenous Amiodarone versus Digoxin in Atrial Fibrillation Rate Control; a Clinical Trial - Shojaee, Majid; Feizi, Bahareh; Miri, Reza; Etemadi, Jalil; Feizi, Amir Hossein (Archives of Academic Emergency Medicine, 2017)
Introduction: Treatment of rapid ventricular response arterial fibrillation (rapid AF) varies depending on the decision of the in-charge physician, condition of the patient, availability of the drug, and the treatment protocol of the hospital. The present study was designed aiming to compare IV digoxin and amiodarone in controlling the heart rate of patients presenting to emergency department with rapid AF and relative contraindication for first line drug in this regard. Method: In the present clinical trial, patients presented to the ED with rapid AF and relative contraindication for calcium channel blockers and beta-blockers were treated with either IV amiodarone or IV digoxin and compared regarding success rate and complication using SPSS version 22. P < 0.05 was considered as statistically significant. Results: 84 patients were randomly allocated to either amiodarone or digoxin treatment groups of 42 (53.6% male). The mean age of the studied patients was 61.8 ± 11.14 years (38 - 79). No significant difference was present regarding baseline characteristics. The rate of treatment failure was 21.4% (9 cases) in amiodarone and 59.5% (25 cases) in digoxin groups (p < 0.001). The mean onset of action was 56.66 ± 39.52 minutes (10 - 180) in amiodarone receivers and 135.38 ± 110.41 minutes (25 - 540) in digoxin group (p < 0.001). None of the patients showed any adverse outcomes of hypotension, bradycardia, and rhythm control. Conclusion: Based on the findings of the present study, rapid AF patients with relative contraindication for calcium channel blockers or beta-blockers who had received amiodarone experienced both higher (about 2 times) treatment success and a more rapid (about 2.5 times) response compared to those who received IV digoxin.